Why farmers deviate from recommended pesticide timing: the role of uncertainty and information. Issue 8 (10th April 2020) - Möhring, Niklas; Wuepper, David; Musa, Tomke; Finger, Robert
Abstract: BACKGROUND: Precise timing of pesticide applications, as recommended by decision‐support systems, can ensure crop protection, while maintaining efficient use of pesticides, yet farmers often deviate from recommended timing strategies. Here, we assess and explain farmersʼ choices to follow or not follow recommendations for the timing of fungicide applications against potato late blight in Switzerland. RESULT: Based on daily fungicide application records as well as regional application recommendations and disease pressure, we found that 36% of applications took place earlier than recommended. Using regression analysis, we identified the exposure to economic risks of infection, susceptibility of the planted potato varieties to late blight infections, as well as yearly differences in disease occurrence as the most important determinants of farmersʼ application decision. CONCLUSION: Our results indicate that decisions to not follow application recommendations and apply early are linked to available information and uncertainty with respect to disease predictions. Based on our results, we make recommendations on how to account for farmersʼ uncertainty with regard to the timing of pesticide applications in the design of pesticide policies and agricultural decision‐support systems. These include the use of new technologies and data, mandatory reporting and tailor‐made taxes and insurance solutions. Although the focus of this article is on late blight in Switzerland, our analysis can easily be extended to other countries and important plant diseases like powdery mildew in grapevines or Fusarium head blight in winter wheat. © 2020 Society of Chemical Industry Abstract : We assess and explain farmersʼ choices to follow or not follow recommendations for the efficient timing of fungicide applications against potato late blight in Switzerland. © 2020 Society of Chemical Industry